Full-Time Employment: An Empirical Study of the Impact of Internet Use in Indonesia - Yunisvita, Yunisvita; Teguh, Muhammad; Ishak, Zulkarnain; Nida, Rahma (International Journal of Economics and Financial Issues, 2024)
The impact of digital transformation era by utilizing the internet has achieved job market outcomes. This study aims to analyze full-time employment probability as a result of using the internet in his work. The data used 8,436 samples from the February 2023 National Labor Force Survey microdl.hilata sorted by formal sector employment. With the analysis technique of the logistic binary regression model, several dominant determinants of the probability to work full-time were obtained. The use of the internet for promotion and marketplace affects labor market outcomes measured by working hours. Probability for workers as full-time workers by using these two things becomes greater. This study also shows that several economic variables such as income, pension security and attending training significantly have a greater effect on workers’ chances of working full-time (>40 h/week). In addition, the influence of demographic variables in the form of age, marital status and domicile of workers in Sumatra provides greater probability for full working hours.